The affect of different light color of physiological conditions of cantang grouper seed (Epinephelus fuscoguttatus lanceolatus) with different size - Lukas, Ade Yulita Hesti; Oedjoe, Marcelien Djublina Ratoe; Sunadji, Sunadji; Suleman, Suleman (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This study consisted of four treatments and three replications, namely the treatment without the addition of light (WL), the addition of green light (G), the addition of blue light (B) and the addition of red light (R). The grouper seeds used are 5-13 cm in size from Gondol Bali. The results showed that fish fry measuring 5-13 cm prefer blue light compared to other light. A total of 56.67% of fish fry choose blue light, followed by green light as much as 25.56%, red light by 11.11% and the lowest in the treatment without light that was 6.67%. The addition of blue light in the rearing container gave the best growth response at a size of 5-13 cm, and the lowest growth response was given to the treatment with the addition of red light. While the number of rod cells was more than cone cells in all treatments with 5-13 cm cantang grouper seed size. However, the highest number of rods and cones was in the treatment WL compared to other treatments. However, the highest growth response occurred in the treatment B and followed by the treatment G, it is presumed that the cone cells found in treatments B and G were dominated by double cone cells which were very sensitive to color, compared to cells. single cone, so that cantang grouper fry respond more quickly to the feed given. While the treatment WL was more dominated by single cone cells.